Antibiotic treatment failure when consulting patients with respiratory tract infections in general practice. A qualitative study to explore Danish general practitioners' perspectives. (2nd October 2017) - Bordado Sköld, Margrethe; Aabenhus, Rune; Guassora, Ann Dorrit; Mäkelä, Marjukka
Abstract: Background: Prescribing antibiotics for acute respiratory tract infections (RTIs) is common in primary healthcare although most of these infections are of viral origin and antibiotics may not be helpful. Some of these prescriptions will not be associated with a quick recovery, and might be regarded as cases of antibiotic treatment failure (ATF). Objectives: We studied antibiotic treatment failure in patients with acute RTIs from a general practitioner (GP) perspective, aiming to explore (i) GPs' views of ATF in primary care; (ii) how ATF influences the doctor-patient relationship; and (iii) GPs' understanding of patients' views of ATF. Methods: Qualitative study based on semi-structured, recorded interviews of 18 GPs between August and October 2012. The interviews started with discussion of a unique case of acute RTI involving ATF, followed by a more general reflection of the topic. Interviews were analysed using qualitative content analysis. Results: In patients with acute RTIs, GPs proposed and agreed to a medical definition of antibiotic treatment failure but believed patients' views to differ significantly from this medical definition. GPs thought ATF affected their daily work only marginally. GPs used many communicative tools to maintain trust with patients in cases of ATF, but they did not consider such incidents to affect the doctor-patient relationship adversely. Conclusion: These findings suggest a possible communication gap between doctors and patients, partly due to a narrow medical definition of ATF. Studies describing patients' views are still missing. General practitioners' experiences and views on antibiotic treatment failure in acute respiratory infections or its effects on the doctor–patient relationship have not been studied previously.